1998
DOI: 10.1071/p97082
|View full text |Cite
|
Sign up to set email alerts
|

Electron Dichroism: Interaction of Spin-polarised Electrons with Chiral Molecules

Abstract: This paper discusses a problem which would be worth studying with (e, 2e) experiments, a technique which has been so successfully used by Erich Weigold: Can spin-polarised electrons distinguish between left-and right-handed molecules? This has been a matter of long-standing discussion and speculation and of controversial experiments. The results presented here show that the attenuation of electron beams passing through chiral molecules is clearly spin-dependent. This is analogous to the circular dichroism of l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…(4) As was predicted theoretically by Farago [22], and by Fandreyer et al [23], the spin-orbit (SO) interaction plays an important role in the formation of the electron dichroism (ED) in the electron scattering from chiral molecules. In corresponding experiments for the scattering of spin-polarized electrons from chiral molecules in the gas phase by Mayer and Kessler [24], Nolting et al [25], and Kessler [26], the scattering cross sections showed a spin-related dependence. While no detectable effect was found in the case of camphor consisting only of light elements, for bromocamphor and other chiral molecules containing at least a heavier atom small asymmetries of the order of 10 −4 were observed.…”
Section: Target Selection and Molecular Structurementioning
confidence: 99%
See 1 more Smart Citation
“…(4) As was predicted theoretically by Farago [22], and by Fandreyer et al [23], the spin-orbit (SO) interaction plays an important role in the formation of the electron dichroism (ED) in the electron scattering from chiral molecules. In corresponding experiments for the scattering of spin-polarized electrons from chiral molecules in the gas phase by Mayer and Kessler [24], Nolting et al [25], and Kessler [26], the scattering cross sections showed a spin-related dependence. While no detectable effect was found in the case of camphor consisting only of light elements, for bromocamphor and other chiral molecules containing at least a heavier atom small asymmetries of the order of 10 −4 were observed.…”
Section: Target Selection and Molecular Structurementioning
confidence: 99%
“…An additional advantage for such a comparison is the rigid bridged structure of both molecules, which eliminates any uncertainty originating from the occurrences of multiple conformations. Furthermore, in analogy to the ED experiments, a possible spin-dependent effect should be considerably stronger in bromocamphor than in camphor due to the Br atom with Z =35 [24][25][26].…”
Section: Target Selection and Molecular Structurementioning
confidence: 99%